Changing conceptions of political morality - Jayal, Niraja Gopal (1995)
"Analyzing the philosophical strands behind the concept, the author emphasises relationship between political morality (PM) and nature of politics at a given point of time. She then examines the shifts - and reasons thereof - witnessed in the perception of PM in India since Independence Stressing tri-polarity of PM - its three poles being citizens, politicians and civil servants - the underscore the need for an active and public spirited citizens body to oversee PM"
Keywords: Public administration - India; Political philosophy - India; Political philosophy